The Mast Cell-Aryl Hydrocarbon Receptor Interplay at the Host-Microbe Interface. (28th October 2018) - Costantini, Claudio; Renga, Giorgia; Oikonomou, Vasilis; Paolicelli, Giuseppe; Borghi, Monica; Pariano, Marilena; De Luca, Antonella; Puccetti, Matteo; Stincardini, Claudia; Mosci, Paolo; Bartoli, Andrea; Zelante, Teresa; et al.
Abstract : Mast cells are increasingly being recognized as crucial cells in the response of the organism to environmental agents. Interestingly, the ability of mast cells to sense and respond to external cues is modulated by the microenvironment that surrounds mast cells and influences their differentiation. The scenario that is emerging unveils a delicate equilibrium that balances the effector functions of mast cells to guarantee host protection without compromising tissue homeostasis. Among the environmental components able to mold mast cells and fine-tune their effector functions, the microorganisms that colonize the human body, collectively known as microbiome, certainly play a key role. Indeed, microorganisms can regulate not only the survival, recruitment, and maturation of mast cells but also their activity by setting the threshold required for the exploitation of their different effector functions. Herein, we summarize the current knowledge about the mechanisms underlying the ability of the microorganisms to regulate mast cell physiology and discuss potential deviations that result in pathological consequences. We will discuss the pivotal role of the aryl hydrocarbon receptor in sensing the environment and shaping mast cell adaptation at the host-microbe interface.